Exploring Factors Influencing House Acquisition Behaviour Among Muslim Generation Y In Malaysia: An Exploratory Factor Analysis Approach - Nik Mohd Fadhil Nik Mohammad; Amalina Mursidi; Muhammad Hamidi Kamaruddin (Universal Publishers, 2026)
Indexed by ERA